2015
DOI: 10.3389/fmolb.2015.00034
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodial HSP70s are functionally adapted to the malaria parasite life cycle

Abstract: The human malaria parasite, Plasmodium falciparum, encodes a minimal complement of six heat shock protein 70s (PfHSP70s), some of which are highly expressed and are thought to play an important role in the survival and pathology of the parasite. In addition to canonical features of molecular chaperones, these HSP70s possess properties that reflect functional adaptation to a parasitic life style, including resistance to thermal insult during fever periods and host–parasite interactions. The parasite even export… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…It has been proposed that nearly 10% of P. falciparum’s proteome is characterized by prion-like repeats and that at least 30% of the proteome is characterized by glutamate/asparagine rich segments [ 21 , 22 ]. For this reason, it is thought that P. falciparum Hsp70s are adapted to fold and stabilize its mis-folding-prone proteome [ 23 , 24 , 25 ]. To this end, we previously demonstrated that a P. falciparum chaperone, PfHsp70-x, which is exported to the parasite-infected red blood cell [ 26 ], exhibits preference for asparagine rich peptides, further suggesting that P. falciparum Hsp70s are primed to bind mis-folded proteins of the parasite [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that nearly 10% of P. falciparum’s proteome is characterized by prion-like repeats and that at least 30% of the proteome is characterized by glutamate/asparagine rich segments [ 21 , 22 ]. For this reason, it is thought that P. falciparum Hsp70s are adapted to fold and stabilize its mis-folding-prone proteome [ 23 , 24 , 25 ]. To this end, we previously demonstrated that a P. falciparum chaperone, PfHsp70-x, which is exported to the parasite-infected red blood cell [ 26 ], exhibits preference for asparagine rich peptides, further suggesting that P. falciparum Hsp70s are primed to bind mis-folded proteins of the parasite [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatic analysis found a correlation between the over-representation of homorepeat containing proteins and the abundance of proteins with putative PrLDs, which were proposed to account for as much as 25% of the parasite proteome ( Singh et al, 2004 ). The biological significance of these protein domains is not clear ( Muralidharan and Goldberg, 2013 ), but P. falciparum has evolved a very efficient proteostatic system to cope with such an aggregation-prone proteome ( Muralidharan et al, 2012 ; Muralidharan and Goldberg, 2013 ; Przyborski et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This process is essential for the development of the parasite and is associated with the pathology of the infection [ 9 , 10 ]. Among the exported proteins are heat shock proteins, functioning as molecular chaperones that are proposed to be highly adapted to the malaria parasite lifecycle [ 11 ]. The heat shock protein 70 (Hsp70) chaperone and its co-chaperone heat shock protein 40 (Hsp40) are involved in facilitating protein folding, stabilization, degradation, and translocation across membranes [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%